Analisa Yuridis Tindak Pidana Narkotika Menurut Pasal 114 Ayat (2) Undang-Undang Nomor 35 Tahun 2009 tentang Narkotika JO Pasal 55 Ayat (1) KUHP: Studi Kasus Perkara No. : 353/PID.SUS/2022/PN.JKT.TIM - Syahmada, Dienda; Arifin, Zaenal; Suherman, Suherman (Jurnal Hukum dan Demokrasi (JHD), 2024)
Narcotics, on the one hand, are drugs or materials that are useful in the field of medicine or health services and the development of science and on the other hand, they can also cause dependence which is very detrimental if they are misused or used without strict and thorough control and supervision; producing, planting, storing, distributing, and/or using Narcotics without strict and thorough control and supervision and contrary to laws and regulations is a Narcotics crime because it is very detrimental and is a very big danger to human life, society, nation and country and Indonesia's national resilience. Based on data from the DKI Jakarta Provincial Narcotics Agency, the number of inmates in Correctional Institutions in DKI Jakarta has reached 70% who are convicted of drug cases, seeing this number where the number of convicts of drug cases almost dominates all Correctional Institutions, we can assume that the drug crime rate in DKI Jakarta is far exceeding the level of crime/other crimes, which is an average of 600 cases per month. Departing from the case above, the problem can be formulated as follows: 1. What are the provisions governing intermediaries for narcotic crimes according to law number 35 of 2009? What are the sanctions against intermediaries for drug crimes according to law number 35 of 2009? In compiling this thesis, the authors use the following methods: 1. Primary data, namely legal materials that are binding, namely in the form of laws relating to capital punishment, 2. Secondary data, namely legal materials that provide an explanation of primary data such as: books, court decisions and others. The conclusions obtained in this research are: 1) The public prosecutor charges the defendant with imprisonment for 7 (seven) years and a fine of Rp. 1,820,000,000.- (one billion eight hundred and twenty million rupiah) subsidiary for 1 (one) year in prison; 2) The Panel of Judges in their decision handed down a 6 (six) year imprisonment and a fine of Rp. 1,820,000,000.- (one billion eight hundred and twenty million rupiah) with the provision that if the criminal fine is not paid then it is replaced with imprisonment for 6 (six) months.